Modification to queueing system M/M/1 with Blum-Blum-Shub generator - Jaffara, M. Z. A. M.; Joey, L. F. L. (IEEE, 2022)
Queueing theory is a mathematical method which is used to investigate the queueing system behavior. In addition, it helps the facilities to build a queueing system for managing the waiting-line. In this paper, the researchers modified a type of queueing model simulation which is called ‘M/M/1’ by using a part of Blum-Blum-Shub algorithm. The simulation results reveals that the arrangement of waiting-line is mostly equivalent in graphs, yet there is a difference in the rate interval boundaries. It becomes lower than the original M/M/1 simulation. That leads to present an indication of predicting the optimal waiting-line to manage the queueing process in consuming a minimal time. More precisely, the total average of mean number of boxes in queue of MM1 and MM1BBS are (0.9027 and 0.2560), and the mean delay in the system evaluated as (0.0481 and 0.03373), while the utilization rates are (0.5498 and 0.5707).